Linking families, learning, and schooling : parent-researcher perspectives - Kabuto, Bobbie; Martens, Prisca (Routledge, Taylor & Francis Group, 2014)
"Parents who are also educational researchers have access to a domain that is highly complex and not always available to other scholars. In this book, parent-researchers provide theoretical and practical insights into children's learning in the home and at school. Readers are given a window into learning in the home context and how all family members organize or engage in that learning. Working on two levels, the book develops scholarly discussions about learning in the home (how is it organized, who the participants are, and what children are learning), and it illustrates the impacts that outside institutions, in particular schools, have on families It is unique in showcasing parent-research as a type of research paradigm with particular aspects and challenges. Both teachers and researchers can learn from these studies as they show the impact that schooling has on families and how institutional discourses and beliefs can both positively and negatively affect the dynamics of any family"--Resumé vydavatele
Keywords: rodina a škola; home and school; studie; studies